Biohydrogen Production From Palm Oil Mill Effluent Using A Thermophilic Semi-Continuous Process With Recycling - Barghash, Sukaina F. A. (2007)
The effluent resulted from the palm oil industry can cause serious pollution if left untreated. This is a problem of considerable magnitude, notably in Malaysia. Anaerobic biological treatment processes, have effectively used to treat POME. Currently, methane production is the most commonly used method to treat POME, but hydrogen production is an innovative alternative because of the methane green house nature. Processes under thermophilic anaerobic conditions showed superior production rates and less variety in fermentation by products which is economically and technically interesting. A fermentation process for hydrogen production by anaerobic micro flora under controlled conditions (pH 5, T 60oC and 200rpm) in a semi-continuous process with recycling was developed for this study. The substrate used in this study was POME (Palm Oil Mill Effluent) and POME sludge for the biogas production was collected to be used as source of inocula. The experimental setup conducted using a 5-L fermenter and six steady states were achieved. The POME sludge possessed a maximum hydrogen evolution rate of 0.83 L H2 gas/Lmed.hr at the fifth steady state with a maximum hydrogen percentage in the biogas of 64% at the fourth steady state. Increasing the organic loading rate from 10.3 to 25.5 kgCOD/m3/d resulted in increasing biomass productivity up to 25.325 g/L at the sixth steady associated with increasing biogas emission throughout the six steady states, and an increase in the total gas yield up to 0.97 L gas/gCOD/d at the fifth steady state. It is also noted that increasing the organic loading rates resulted in increasing hydrogen yield up to 0.6 L gas/g COD/d at the fifth steady state, and decreasing the COD removal efficiencies from (66.33 to 59.32%) throughout the system, this might be due to the decrease of hydraulic retention time (HRT) and solids retention time (SRT) from 5 to 2.94 days and 52.282 to 12.260 days, respectively. The minimum solids retention time (SRTm) for this study was 1.99 days. A mathematical model was developed to understand the kinetics of the digester operations. The growth yield coefficient, Y and the specific microorganism death rate, kd for anaerobic semi-continuous system, were found to be 0.3075 (gVSS/gCOD) and 0.1035 day-1 respectively. The maximum specific growth rate, μmax , maximum substrate utilization rate, K, half-velocity coefficient, Ks for the process were found to be 0.502369 day-1,1.63372gCOD/gVSS.day, 50.336546 mgCOD/l respectively. This study suggests that using thermophilic semi-continuous process with recycling is suitable for hydrogen production from POME and POME biomass and increasing the organic loading rate esulted in an increase of biogas production throughout the system.